Assessment of Cold Chain System for Routine Immunization of Primary Health centres of the Bhojpur district of Bihar - Pandey, Sanjay; Singh, C M; Ranjan, Alok; Kumar, Yogesh; Kumar, Pragya; Agarwal, Neeraj (Indian Journal of Community Health, 2018)
Background: Immunization is an important among activity in the Public Health Services. The vaccines are highly temperature sensitive and vaccine potency once lost cannot be restored. A well-managed cold chain will increase the efficiency of immunization and reduce vaccine wastage. An assessment of cold chain system for vaccine storage was done in the all PHCs of the study area. Aims & Objectives: To evaluate the cold chain practices, with particular reference to assessing the availability of cold chain equipment, vaccine storage practices, monitoring of cold chain in primary health centres (PHCs) of Bhojpur district. Material & Methods: A cross-sectional study was conducted at all the cold chain points of 14 PHCs of Bhojpur district during January to May 2015. A predesigned, pretested checklist was used by the trained investigators during their visits. The information was evaluated on the basis of important components related to the cold chain points. Results: All the PHCs had a dedicated cold chain room with sufficient number of cold chain equipment. Consolidated effective vaccine management score for cold chain points of 8 (57.1%) PHCs were average (60-79%). None of the PHCs have satisfactory score (? 80%). Vaccine storage practice and availability of complete RI micro-plan were found satisfactory at 12 (85.7%) PHCs. Maintenance of cold chain equipment were satisfactory at 10 (71%) PHCs. But, temperature monitoring. (5) (35.7%) and waste disposal related to routine immunization 3 (21.4%) PHCs were disappointing. Conclusion: The primary health centres had average performance related to the cold chain system, which is a matter of concern warranting for the cold chain monitoring. We recommend supportive supervision as the key measures in improvement of cold chain system.